2006
DOI: 10.1016/j.pbb.2006.09.014
|View full text |Cite
|
Sign up to set email alerts
|

α-Ethyltryptamine (α-ET) as a discriminative stimulus in rats☆

Abstract: Abstractα-Ethyltryptamine (etryptamine, α-ET) is a drug of abuse that first appeared on the clandestine market in the mid 1980s. Its pharmacological actions are poorly understood. In this investigation, it is reported for the first time that α-ET serves as a training drug in drug discrimination studies. Male Sprague-Dawley rats were trained to discriminate (30-min pretreatment time) 2.5 mg/kg of α-ET (ED 50 = 1.3 mg/kg) from saline vehicle using a standard two-lever operant paradigm and a VI-15s schedule of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…α-ET fully substitutes for MDMA in MDMA-trained rats ( Glennon, 1993 ; Glennon et al, 2006 ), supporting the notion that its qualitative effects are comparable with those of the latter. However, there seems to be some confusion in the literature about the distinct effects of the two enantiomers of α-ET.…”
Section: Other Potential Substitutessupporting
confidence: 60%
“…α-ET fully substitutes for MDMA in MDMA-trained rats ( Glennon, 1993 ; Glennon et al, 2006 ), supporting the notion that its qualitative effects are comparable with those of the latter. However, there seems to be some confusion in the literature about the distinct effects of the two enantiomers of α-ET.…”
Section: Other Potential Substitutessupporting
confidence: 60%
“…A study by Hong et al addressed the possibility that the optical isomers of 7d may each be responsible for one of the observed properties by conducting discriminative stimulus assays using (+)-amphetamine, 2,5-dimethoxy-4-methylamphetamine (DOM), and MDMA. 37, 38 It was found that (−)- 7d generalized to (+)-amphetamine and MDMA, but only partially to DOM, and that (+)- 7d generalized to DOM and MDMA, but only partially to (+)-amphetamine. The authors concluded that while there was significant variance in effects of individual animals, the amphetamine-like properties of 7d primarily resided in the (−)-isomer.…”
mentioning
confidence: 99%
“…α-ET was first synthesized in 1947 as a potential synthetic precursor to the β-carbolines but appeared on the clandestine market as an antidepressant (Monase) in the mid-1980s [63]. In 1986, Daldrup et al described its first illicit use in Germany [64] and in 1993 the U.S. Drug Enforcement Administration (DEA) included it on the Schedule I list [65].…”
mentioning
confidence: 99%